Association Between the Use of the Sahabat Hipertensi Self-Assessment Application and Preventive Lifestyle Behavior Among Adults at Risk of Hypertension - Bobi Handoko; Asep Marzuki; Anastasya Shinta Yuliana; Sherly Mutiara (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background of study: Hypertension is a major public health issue because it often goes unnoticed until complications arise. Mobile health applications offer a practical way to support self-assessment, risk awareness, and behavior change. This study examines whether the Sahabat Hipertensi app influences preventive lifestyle behavior among adults at risk of hypertension, using the combined perspectives of the TAM and the HBM. Methods: A quantitative explanatory study was conducted with 200 adults aged 25-60 years who had at least one risk factor for hypertension. Participants completed a 30-item Likert questionnaire measuring perceived usefulness, susceptibility, severity, an intention to use, actual use, and preventive lifestyle behavior. Structural relationships were analyzed using SmartPLS 4. Results: The model measurement demonstrated satisfactory validity and reliability. Structural analysis showed that perceived usefulness (beta value 0.612, p less than 0.001), perceived usefulness influenced the intention to use (beta value 0.351, p less than 0.001), perceived susceptibility impacted the intention to use (beta value 0.214, p value 0.003), and perceived severity affected the intention to use (beta value 0.197, p value 0.008). Actual use was significantly linked to preventive lifestyle behavior (beta value 0.762, p less than 0.001). The model explained 58% of the variance in healthy behavior. Conclusion: The Sahabat Hipertensi app plays a significant role in promoting preventive lifestyle behavior among adults at risk of hypertension. Combining TAM and HBM offers an effective framework for understanding the adoption of hypertension self-assessment technology in community health settings.